Measurement and visualization of airflow through sports textiles - Brownlie, L.; Bailey, C.; Carbo, J.; Judelson, D.; Ostafichuk, P.; Allison, J.; Rival, D. (Proceedings, 2020)
In marathon running, maintenance of body temperature is critical for peak performance. Race apparel should maximize ventilation yet current fabric permeability standards are based on airflow rates that are not generated during running. A novel flow measurement device was used to measure airflow through textiles and the effects of fabric hole size, coverage area and standoff distance between a simulated torso and fabric at velocities of 3.3, 5.3 and 10 m.s-1. Fluorescent dye injection in a tow tank or flume permitted visualization of flow through fabrics. Ventilation is constrained by the low flow velocity in the stagnation area over the chest of an athlete, with freestream airflows of 3.3 and 10 m.s-1 reduced to 1.31 +/- 0.10 m/s (39.6%) and 3.51 +/- 0.27 m.s-1 (35.0%), respectively at a yaw angle of 20°. The initial low flow velocity precludes improvements in airflow despite changes in the standoff distance, fabric hole size or coverage area.